2016
DOI: 10.1037/xlm0000248
|View full text |Cite
|
Sign up to set email alerts
|

Logic brightens my day: Evidence for implicit sensitivity to logical validity.

Abstract: A key assumption of dual process theory is that reasoning is an explicit, effortful, deliberative process. The present study offers evidence for an implicit, possibly intuitive component of reasoning. Participants were shown sentences embedded in logically valid or invalid arguments. Participants were not asked to reason but instead rated the sentences for liking (Experiment 1) and physical brightness (Experiments 2-3). Sentences that followed logically from preceding sentences were judged to be more likable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
175
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(200 citation statements)
references
References 40 publications
(77 reference statements)
17
175
7
1
Order By: Relevance
“…Crucially this effect was uninfluenced by participants cognitive capacity, mindset or superficial problem structures, features that did influence explicit reasoning judgments. We have recently shown that validity not only influences how much participants like a presented statement, but also their perceptual judgments concerning its brightness, a feature completely disconnected from its logical validity (Trippas, Handley, Verde & Morsanyi, 2016). It has been suggested that this effect arises because of a feeling of fluency arising from reading a series of logically coherent sentences that in turn generates a feeling of positive affect which is then misattributed to the perceptual features of the stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially this effect was uninfluenced by participants cognitive capacity, mindset or superficial problem structures, features that did influence explicit reasoning judgments. We have recently shown that validity not only influences how much participants like a presented statement, but also their perceptual judgments concerning its brightness, a feature completely disconnected from its logical validity (Trippas, Handley, Verde & Morsanyi, 2016). It has been suggested that this effect arises because of a feeling of fluency arising from reading a series of logically coherent sentences that in turn generates a feeling of positive affect which is then misattributed to the perceptual features of the stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that intuitive sensitivity to logical structure arises because logical arguments are more fluent; that is, it is easier to integrate the premises of a logically valid argument than one that is not (Morsanyi & Handley, 2012). Increased fluency is thought to lead to increased positive affect which has been shown to result in higher ratings of liking for valid than invalid arguments (Morsanyi & Handley, 2012;Trippas, Handley, Verde & Morsanyi, 2016). Most recently, it has been shown that the conclusions of valid arguments are judged to be brighter on a perceptual judgment task, presumably because a feeling of positive affect is misattributed to the perceptual features of a valid conclusion that follows fluently from its premises .…”
mentioning
confidence: 99%
“…Although people are not instructed to reason, they nevertheless indicate that they like valid conclusions more than invalid ones and judge them to be brighter (Trippas, Handley, Verde, & Morsanyi, 2017).…”
Section: Logic-liking Paradigmmentioning
confidence: 99%
“…However, recent studies have explored the possibility of a reversed phenomenon, that is, the possibility that the logical validity of an argument may bias judgments of believability. These studies presented participants with inferences where logic and belief were in accordance or in conflict and instructed them to evaluate their conclusions’ believability (Handley & Trippas, 2015; Trippas, Thompson, & Handley, 2017) or likability and brightness (Trippas, Handley, Verde, & Morsanyi, 2016) in a short period of time. They found that people needed more time and were more prone to errors when the logical validity of the problems conflicted with the conclusion’s believability.…”
Section: Introductionmentioning
confidence: 99%